Comparativo de tres tipos de bosque en la producción de biomasa y stock de carbono en los distritos de San Juan Bautista, Mazán e Indiana, Loreto, 2020 - Gronerth Escudero, Olguita (2021)
The Amazonian forests are considered one of the largest carbon sinks, however, there is little information on the carbon stock in them. This information would be very important to assess the CO2 sequestration environmental service and offer it on the carbon market. The objective of this study was to quantify the biomass and carbon stock of low-terrace, mid-terrace and low-hill forests located in the Loreto region, Peru. The results show that the low-terrace forest contains a total carbon stock of 11 088,88 tC and 8,28 tC/ha, where V. albidiflora contains the highest carbon stock of 1512,24 tC and 1,13 tC/ha and the diameter class from 60 cm to 69 cm contains the largest carbon stock of 2371,78 tC and 1.77 tC/ha; in the mid-terrace forest a total of 2834,07 tC and 157,45 tC / ha are reported, where E. alvidiflora contains the highest carbon stock of 302,04 tC and 16,78 tC / ha and the diameter class of 40 cm to 49 cm contains the largest carbon stock of 921 tC and 51,17 tC/ha; in the low-hill forest 41 604.51 tC and 23.028 tC / ha are reported, where Otoba sp. contains the highest carbon stock of 3726 tC and 2,06 tC/ha and the diameter class from 60 cm to 69 cm contains the highest carbon stock of 9818,25 tC and 5,43 tC/ha. The non-parametric Kruskal-Wallis test indicates that there is a significant difference between the averages of the carbon stock between the three types of forest (p-value = 0,00 < ? = 0,05).